Polymorphism of Haemoglobin-e in Selected Malaysian and the Maldives Populations - Saleem, Mohamed (2011)
Human β-globin gene cluster is composed of five functional genes and a pseudogene. Haemoglobin E gene is the result of a point mutation (GAG→AAG) in the 26th codon of this β-globin gene. This mis-sense mutation, inherited as autosomal recessive trait, codes for lysine instead of glutamic acid. From the many haemoglobinopathies around the world, HbE is the commonest in Southeast Asia, and encountered in high frequencies in Khmer peoples living in the borders of Cambodia, Thailand and Laos. It is found at high frequencies in the Malaysian-Malays and in some islands of Maldives. Haplotype frequencies of E chromosomes were studied in a sample from Maldives islands and three major ethnic groups of Malaysia including Malays, Chinese and Indians using the conventional restriction fragment length polymorphic markers and single nucleotide polymorphism markers. Various descriptive and inference statistics based on different models of population genetics perspective were used to understand how the molecular diversity of HbE allele varies at individual level and at population level and to infer the mutational age. HbE mutation in all these four sub-populations were associated with at least three RFLP haplotypes H1 (–+–+++–), H2 (+––––+–) and H3 (–+–++–+) which makes 81-93% of the total. Majority of these RFLP haplotypes were framework-2, and few appeared on framework-3. SNP haplotypes in these four samples also revealed the HbE allele was associated with at least three different haplotypes, Hap01 (GAAGTTCCCAACACTTCAC), Hap02 (CAGGTCCCCAACACTTCGC) and Hap03 (GAAGTTGCCGACCTTTCAC) making 86-91% of the total. Analysis of molecular variance on the RFLP haplotypes and SNP haplotypes found most of the haplotype frequency variations were distributed among individuals within the subpopulations, and an average of 1-3 % variations were seen between the samples. A significant population differentiation, revealed by FST statistic, was found between Malaysian-Chinese and the rest of the samples. This substructure was probably a result of restriction in gene flow showing the genetic isolation. Rest of the samples were reasonably homogenous to each other and lacked genetic structuring between them. Phylogenetic analysis using the genetic distance of these haplotypes showed that Maldivians sample was closely related to samples from Malay and Indian subpopulations. Using the theory of coalescent simulations the average age of the HbE mutation was estimated to be 2488 years for SNP haplotypes and 2615 for RFLP haplotypes. This finding suggests that HbE is a recent mutation in evolutionary time scale and supports multiple origin and distribution through population migration. Population genetic analysis of the HbE allele for these four populations in this study indicates a complex interplay of recombination, balancing selection and genetic drift acting to maintain the common haplotypes at high frequencies